Oral Oncology: Two elective courses for advanced undergraduates - An Argentine teaching experience - Gerardo Gilligan; María Fernanda Galindez Costa; Eduardo Piemonte; Jerónimo Lazos; René Panico (Oral Oncology Reports)
The COVID-19 pandemic prompted significant adaptations in educational practices at Universidad Nacional de Córdoba, including the integration of e-learning and virtual education modalities. In response to an observed increase in advanced-stage oral cancer cases post-2020, we developed new educational strategies aimed at OC prevention and awareness. This study presents our experience with an innovative undergraduate program focusing on Oral Oncology and Oral Potentially Malignant Disorders. Two elective courses were integrated into the curriculum, featuring contributions from Oral Medicine and Pathology experts across several Latin American countries via virtual platforms. Each course provided comprehensive training, including clinical practice and telemedicine protocols for early lesion identification. A total of 107 students successfully completed the courses, highlighting the program's effectiveness in enhancing student engagement and competence in OC prevention. Recommendations from this initiative include reinforcing undergraduate curricula with OC-focused education and promoting international collaboration in higher education for comprehensive training. Future research should assess the long-term impact of such programs on early OC diagnosis and patient referral practices.